2016
DOI: 10.1159/000448987
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Catestatin in Patients with Acute Coronary Syndrome

Abstract: Objectives: To measure plasma catestatin levels in patients with acute coronary syndrome and investigate whether there is an association between catestatin levels and long-term outcome. Methods: Patients (n = 170) with suspected acute coronary syndrome who underwent emergency coronary angiography were enrolled, including 46 with acute ST-segment elevation myocardial infarction (STEMI), 89 with unstable angina pectoris (UAP), and 35 without coronary artery disease (CAD). All patients were followed for 2 years t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
1
10
0
5
Order By: Relevance
“…24 Conflicting results have been recently reported by increased or decreased plasma levels of catestatin in patients with coronary artery disease (CAD). [25][26][27][28][29] Therefore, the precise effects of catestatin on arteriosclerosis have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…24 Conflicting results have been recently reported by increased or decreased plasma levels of catestatin in patients with coronary artery disease (CAD). [25][26][27][28][29] Therefore, the precise effects of catestatin on arteriosclerosis have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we hypothesized that in adult rat cardiomyocytes Cts could increase the first step in cardiac glucose metabolism and glucose uptake mediated by the Glut4 transporters, by inducing Glut4 translocation to the plasma membrane. We used 10 nM Catestatin, a mildly high concentration with respect to the plasmatic level measured in healthy subject [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, those with increased plasma catestatin and BNP were at highest risk of all-cause and cardiac death. Xu et al, studied patients with acute ST-segment elevation myocardial infarction (STEMI, n=46), unstable angina pectoris (n=89), and no coronary artery disease (n=35) [186]. They found that plasma catestatin levels were lower in the STEMI and unstable angina groups compared to controls.…”
Section: 0 Additional Neuropeptidesmentioning
confidence: 99%